A study on health related risk factors and health seeking behavior among elderly population in rural Bangladesh - Ferdaus, Farhana; Zahan, Refat; Rahman, Md Abdur; Chowdhury, Shahin (Mediscope, 2020)
Globally, 10% of the world population is elderly people and it is expected to increase to 21% in the year 2051. In the year 2002, the number of elderly people in the world was estimated to be 605 million, which is expected to rise to more than 1.2 billion by the year 2025. This crosssectional study was conducted to and out the health-related quality of life and risk factors among elderly population in the selected rural population of Shyamnagar Upazila of Satkhira District. Data was collected from both the male and female population, aged 60 years and above, during February to June 2018. Purposive sampling technique was used to collect data from 50 respondents by face to face interview with semi-structured questionnaire. In the study, the mean age of elderly was male 63 (±2.95) years, and female 61.8 (±2.04) years. Other socio-demographic factors among elderly were as follows: 20 (40%) of elderly were illiterate, 15 (30%) of elderly were doing business, 21 (42%) were doing farming. 40 (80%) of elderly were married. The study also reported the five most common disease co-morbidities for elderly which included: 71.43% male and 28.57% female had hypertension while 72.22% of male and 27.78% of female patients were already treated, 68.75% male and 31.25% female had diabetes mellitus and 100% of them were treated, 50% of male elderly and 50% of female elderly were suffering bone and joint pain/arthritis and 60% of them were received treatment, hearing impairment found among 100% of male while two-third of patients received treatment, one-third of female and two-third of male elderly suffered from poor vision; however, only one-third of female patients were treated. On the basis of these findings, it can be recommended that there is a need to develop geriatric health-care services. Mediscope Vol. 7, No. 2: July 2020, Page 75-81